Effect of nutrient management on yield, quality and economics of irrigated Indian mustard (Brassica juncea) - SINGH, YOGESHWAR; SINGH, TARKESHWAR; SINGH, U N; RAJPUT, P K (The Indian Journal of Agricultural Sciences, 2010)
A field experiment was carried out during winter seasons of 2004 to 2006 on sandy loam soils of Varanasi to study the effect of different levels of nitrogen (50, 100 and 150 kg N/ha), sulphur (0, 30 and 60 kg S/ha) and zinc (0, 0.5 and 1.0 kg ZnEDTA/ha) on growth, yield attributes, yield, quality and economics of Indian mustard [Brassica juncea (L.) Czernj & Coss.]. Significant improvement in growth parameters and seed and stover yields were observed up to 150- 30- 0.50 kg N-S- Zn EDTA/ha, respectively. The values of oil and protein content, nutrient contents and their acquisition; oil and protein yields had the highest affinity with the highest levels of N, S and Zn. The acid value significantly increased with increasing rates of nitrogen up to 150 kg N /ha and sulphur up to 60 kg S /ha, while decreased with zinc application where highest value was associated with control. The mustard crop fertilized with 150-30-0.50 kg N-S- Zn EDTA /ha fetched the highest net returns with maximum benefit : cost ratio.